A Review of Research on International Chinese Teachers AI Literacy and Teaching Self-Efficacy - Guan, Hanyu (Education Insights, 2026)
This research article examines the AI literacy and teaching self-efficacy of international Chinese teachers, exploring their preparedness to integrate artificial intelligence into educational practices. The study begins with a comprehensive review of the theoretical frameworks surrounding AI literacy and self-efficacy, followed by an empirical investigation into the current state of these competencies among international Chinese educators. Using a mixed-methods approach, the research identifies key factors influencing AI literacy and self-efficacy, including professional training, teaching experience and institutional support. Results reveal significant disparities in AI literacy levels and self-efficacy across different demographic groups, highlighting the need for targeted interventions. The discussion emphasizes the implications of these findings for teacher training programs and policy development. The article concludes by proposing actionable strategies to enhance AI literacy and self-efficacy among international Chinese teachers, fostering their ability to navigate the evolving educational landscape.